Artificial Intelligence and Maritime Governance: Policy Challenges in Combating Illegal Fishing in the Natuna Exclusive Economic Zone - Cintya Yelena Putri; A. Adang Supriyadi; Abdul Rivai Ras (International Journal of Education, Vocational and Social Science, 2025)
The Natuna Exclusive Economic Zone (EEZ) is one of Indonesia’s most strategic maritime areas, facing persistent threats from illegal, unreported, and unregulated (IUU) fishing that undermine national sovereignty, food security, and marine sustainability. Conventional maritime patrols have proven inadequate due to limited resources, adverse weather, and the vastness of the region. This study explores the role of artificial intelligence (AI) in strengthening maritime governance, with particular attention to policy challenges in addressing IUU fishing in the Natuna EEZ. Using a qualitative-analytical case study approach, the research identifies major issues such as inter-agency coordination, legal recognition of digital evidence, and community participation in surveillance efforts. The findings show that AI can enhance maritime monitoring through multisensor data integration, trajectory prediction, and anomaly detection in vessel movements. However, the effectiveness of AI systems depends on institutional interoperability, legal adaptation, and inclusive governance mechanisms. The study concludes that AI integration in maritime governance represents a multidimensional reform rather than a purely technical advancement. It bridges technology, law, and environmental management, positioning AI as a strategic instrument to safeguard Indonesia’s maritime sovereignty and strengthen its contribution to Indo-Pacific security cooperation.